If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27x + -11 + -15x = 3(4x + -5) + 4 Reorder the terms: -11 + 27x + -15x = 3(4x + -5) + 4 Combine like terms: 27x + -15x = 12x -11 + 12x = 3(4x + -5) + 4 Reorder the terms: -11 + 12x = 3(-5 + 4x) + 4 -11 + 12x = (-5 * 3 + 4x * 3) + 4 -11 + 12x = (-15 + 12x) + 4 Reorder the terms: -11 + 12x = -15 + 4 + 12x Combine like terms: -15 + 4 = -11 -11 + 12x = -11 + 12x Add '11' to each side of the equation. -11 + 11 + 12x = -11 + 11 + 12x Combine like terms: -11 + 11 = 0 0 + 12x = -11 + 11 + 12x 12x = -11 + 11 + 12x Combine like terms: -11 + 11 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| p-88-18=72/5(h-7) | | 9(m-3)-7m=2(m-13)-1 | | 16x^3-36=0 | | 6*22/7 | | -88-18=72/5(h-7) | | 12+2x+10=3x+18-5x | | 5b+7=b-2 | | 256-9x=20 | | (v^15y^-6)^7/3 | | 4(-4)+10y=40 | | Y-18-36Y=3 | | f/6-1.2=-30 | | 9x-12=19x | | 1/2x+9=36 | | 3a-8=4a+3 | | (-3)(-3)-5=8-2x | | (v^15y^-6)7/3 | | 6x-2(x-1)=8x+15-3x | | 7x+37=32 | | Y=x^2+3x-22 | | 3(-12z-5)+10=12(-3z+5)-61 | | p-88=72/5(88-7) | | 7.5+0.5x+3/4x | | 7p+22p+3=0 | | p-17/1=72/5(-7) | | p-17/2=72/5(-7) | | 10x+9=66 | | p-17/5=72/5(-7) | | p-17=72/5(-7) | | (5x^3)-4x=76 | | 2x^2+21x-36=0 | | y=-1/2*4-4 |